Genome-wide survey of the HMA gene family in wheat (Triticum aestivum L.) and its potential role in cadmium stress - Leilei Shao; Xuyu Guo; Yang Wang; Tianzhen Lei; Yijie Wan; Lingjian Ma; Na Niu (BMC Genomics)
Abstract Cadmium has been accumulating in the agricultural and ecological environment in recent years due to the release of industrial pollutants. Due to its high solubility, slow degradability and high toxicity, it is highly susceptible to occurring in agricultural fields. The presence of cadmium at low concentrations is harmful to plants. Heavy metal ATPases (HMAs) are proteins that can detoxify high concentrations of heavy metals through vacuole compartmentalization or exocytosis pathways. They have been extensively studied in plants. However, the cadmium transport function of HMAs in wheat has not been explored. In this study, a comprehensive and systematic investigation of HMA gene family members in wheat was conducted. A total of 28 putative TaHMAs were identified. Phylogenetically, these 28 putative TaHMAs were divided into two subgroups: Cu/Ag and Zn/Co/Cd/Pb. The gene structures and conserved motifs were consistent within the same branch and diverse in different branches. The TaHMA gene family is closely related to rice, B. distachyon and A. tauschii. GO analysis results suggest that TaHMAs may be involved in cation transport and membrane components. Protein interaction analysis results suggest that TaHMAs may interact with TaSOD to activate the SOD defense mechanism in wheat. Expression patterns exhibited tissue specificity. Finally, the expression patterns of TaHMAs were validated in the roots and leaves of wheat plants under cadmium stress. Our findings will be valuable for functional studies and applications of HMA gene family members in wheat.